An introduction to lambda calculus [ - Ricci, Raven (New York : Learning Press, 2014)
This book provides a comprehensive introduction to Lambda Calculus
1. Introduction to lambda calculus -- 2. Church encoding -- 3. Fixed point combinator -- 4. Binary lambda calculus -- 5. Anonymous function -- 6. Apply and director string -- 7. Explicit substitution and lambda lifting -- 8. Normalisation by evaluation and SKI combinator calculus -- 9. Simply typed lambda calculus and system F -- 10. Beta normal form and calculus of constructions
Keywords: Lambda calculus